Understanding lay-public perceptions of energy storage technologies: Results of a questionnaire conducted in the UK. (October 2018) - Jones, Christopher R.; Gaede, James; Ganowski, Sara; Rowlands, Ian H.
Abstract: Grid-scale electrical energy storage technologies (ESTs) are a means of tackling the challenges of introducing more intermittent power generators into national electricity networks. Public perceptions of emerging technologies are known to affect the likelihood of their commercial success; however, there is a paucity of research into the nature and antecedents of lay-public perceptions of grid-scale ESTs. We report on the findings of an online survey distributed to a diverse sample of the UK ( N =1, 044) designed to address this gap. The focus was on four grid-scale options (i.e. pumped hydro storage, compressed air energy storage, flywheels and lithium-ion batteries). Broadly, respondents were favourable to all technologies, although there was a preference for pumped hydro storage. Regression analysis revealed that intentions to support ESTs were positively predicted by attitudes, positive affect, perceived benefits, trust in developers, self-claimed awareness of ESTs and a belief that financial expenditure on the technology is warranted. Pro-ecological values were a negative predictor. Possible explanations for and implications of the findings are discussed.